DR.PHILIPPE W. CABRAL DE VASCONCELLOS, O GRANDE PRESTADOR DE SERVIÃ‡OS Ã COMUNIDADE - Mattos, Jairo Ribeiro de (REVISTA DE AGRICULTURA, 2015)
DR.PHILIPPE W. CABRAL DE VASCONCELLOS, O GRANDE PRESTADOR DE SERVIÃ‡OS Ã COMUNIDADE